Temporal occurrence and species composition of birds on artificial feeding sites maintained for game mammals in the Dinaric Mountains, Slovenia - Bordjan, Dejan; Soultan, Alaaeldin; Jerina, Klemen (Ornis fennica, 2023)
Artificial feeding is a widely used management tool, but it often attracts nontarget species, including birds, to permanent feeding sites. This study used camera traps to monitor the presence of birds at selected sites used for bear management in Dinaric forest. A large number of bird species (35) were recorded, representing roughly half of all species breeding in the surrounding area. These species were grouped based on monthly and hourly presence, and corresponded to food groups, with most belonging to granivores or scavengers. Some species, such as Pigeons (Columba sp.), Raven (Corvus corax) and Buzzard (Buteo buteo), adapted their presence to the availability of food at the feeding sites, while others were not affected by this. Both Chaffinches (Fringilla coelebs) and Jays (Garrulus glandarius) frequented the feeding sites, but their temporal presence was influenced by their biology rather than by food availability. The Sparrowhawk (Accipiter nisus) also adapted its presence to food availability, and its presence was closely associated with that of the Jay. This study confirms the temporal differences in the use of feeding sites by birds and mammals, which is likely due to their different biology and past management. This can be used to make wildlife management more efficient and reduce the undesirable effects of artificial feeding.